Prosedur, Tantangan, dan Solusi dalam Penerapan Sistem Kliring Nasional pada Bank Sumsel Babel Kantor Kas Cabang Jakabaring - Melia Sari; Fitriasuri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the procedures, challenges, and solutions in the implementation of the National Clearing System of Bank Indonesia (SKNBI) at Bank Sumsel Babel Cash Office Jakabaring Branch. The research is motivated by the importance of efficient, secure, and affordable payment systems in supporting banking operations, particularly in interbank fund transfer transactions with competitive costs. The research method employs a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Primary data sources were obtained directly from Bank Sumsel Babel Cash Office Jakabaring Branch employees, including Tellers, Customer Service, and Cash Office Heads, as well as SKNBI service users. The results show that SKNBI implementation procedures at Bank Sumsel Babel Cash Office Jakabaring Branch are generally in accordance with Bank Indonesia regulations, although there is an adjustment in service hours ending at 3:00 PM compared to BI's regulation until 4:45 PM. The main challenges faced are operational risks due to human error, such as incomplete form filling by customers, incorrect account number and recipient name entries, and difficulties in identifying less familiar destination banks. Consequently, officers must perform manual re-verification which is time-consuming and potentially causes transaction returns. The solutions implemented include improved administrative accuracy by officers, more assertive customer education, data re-verification through internal systems, and priority reprocessing of transactions in the event of returns. This study concludes that SKNBI implementation at Bank Sumsel Babel Cash Office Jakabaring Branch has been effective, supported by a two-way commitment between the bank and customer discipline.